Peningkatan Hasil Belajar Memahami Pengetahuan Dasar Teknik Mesin (PDTM) Menggunakan Model Team Games Tournament (TGT) Siswa Kelas X Teknik Pemesinan SMK Negeri 6 Malang - Muhammad Sujatmiko (RC-INSTITUT, 2020)
This Classroom Action Research aims to determine the learning process of Basic Knowledge of Mechanical Engineering using the Team Games Tournament (TGT) model for Class X Students of Mechanical Engineering at SMKN 6 Malang and student responses in improving learning outcomes and increasing learning outcomes of Basic Knowledge of Mechanical Engineering for Class X Students of Mechanical Engineering at SMKN 6 Malang Team Games Tournament (TGT) model. The research method used was Classroom Action Research with two cycles. The results show that the improvement of the learning process using the Teams Games Tournament (TGT) model in the subject of Basic Knowledge of Mechanical Engineering (PDTM) Class X Mechanical Engineering students of SMKN 6 Malang has been going well. Based on the results of observations and observations made during the action process, it can be concluded that using the Teams Games Tournament (TGT) learning model can improve the learning process, thus showing students to be motivated, active and innovative in the implementation of learning in class. The Team Game Tournament (TGT) learning model can improve student learning outcomes on the competency standards of Basic Knowledge of Mechanical Engineering (PDTM) in Class X Mechanical Engineering Students of SMKN 6 Malang. The increase can be seen before the action is taken as many as 12 students or 40% of students complete according to the KKM standard (75). In Cycle I, the increase also increased to 20 students or 66.67%. Then in the last action or cycle II there was an increase again of 33 students completed or 100%. This illustrates that with the Teams Games Tournament (TGT) learning model, student learning outcomes are better than before. Learning using the Team Game Tournament (TGT) model can provide a positive response to students. This means that students are happier in following MPDPL subjects.